Seasonal variations in self-determined motivation and symptoms of burnout and overtraining among top level cross-country skiers. - Heggebø, F.; Lemyre, P. N.; Nilsen, D. A.; Pensgaard, A. M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Fulfillment of the three basic needs for autonomy, competence and relatedness is crucial for individual development and well being [1]. The quest to fulfill these basic needs and whether one is successful at it will affect the quality of the motivation to initiate and pursue an activity. Thwarting basic needs and participating in sports for extrinsic reasons are believed to affect well being and lead to maladaptive behavioral outcomes [1]. Contemporary research in athlete burnout has suggested that seasonal variations in self-determined motivation are meaningfully linked to symptoms of burnout in elite athletes [2,3]. Athlete burnout is defined as a syndrome of "physical and emotional exhaustion, sport devaluation, and reduced sense of accomplishment" [4], and symptoms of overtraining have been found to be a precursor of athlete burnout [2]. Thus, the aim of this study was to add to the current body of knowledge and study how motivation and overtraining symptoms are linked to the development of burnout at a crucial training period of the season in elite x-c ski racers. Method: A sample of elite Norwegian cross-country skiers (n = 32) aged from 18-23 years (Mode = 18), and training 700-800 hours a year participated in this study. Data were collected in November, in the pre-competitive phase, using the ABQ, SMS and SOSQ. Results: Findings yielded a negative moderate relationship between self-determined motivation and burnout. Intrinsic motivation was moderately negatively related with the devaluation of the sport experience. A positive moderate relationship emerged between the emotional and physical exhaustion and externally regulated motivation. Additionally, amotivation was positively linked to burnout and the devaluation of the sport experience. Finally, results indicate that when athletes display high levels of self-determined motivation, overtraining symptoms are low; however when levels of self-determined motivation were low athletes experiences elevated symptoms of overtraining. Conclusions: Current results support previous study findings in that levels of self-determined motivation in elite cross country skiers are meaningfully linked to overtraining and athlete burnout symptoms. 1. Deci, E.L., & Ryan, R.M. (2000). The "what" and "why" of goal pursuits: Human needs and the self determination of behavior. Psychol Inq 2000: 11, 227-268 2. Lemyre, P-N., Roberts, G.C., & Stray-Gundersen, J. (2007). Motivation, overtraining, and burnout: Can self-determination predict overtraining and burnout in elite athletes? European Journal of Sport Science, 7, 115-126. 3. Lemyre, P-N., Treasure, D.C., & Roberts, G.C. (2006). Influence of Variability in Motivation and Effect on Elite Athelete Burnout. Journal of Sport and Exercise Psychology, 12, 32-48. 4. Raedeke, T.D. (1997). Is athlete burnout more than just stress? A sport commitment perspective. Journal of Sport and Exersice Psychology, 19, 396-417.